2014
DOI: 10.1002/cbic.201402128
|View full text |Cite
|
Sign up to set email alerts
|

Computational Library Design for Increasing Haloalkane Dehalogenase Stability

Abstract: We explored the use of a computational design framework for the stabilization of the haloalkane dehalogenase LinB. Energy calculations, disulfide bond design, molecular dynamics simulations, and rational inspection of mutant structures predicted many stabilizing mutations. Screening of these in small mutant libraries led to the discovery of seventeen point mutations and one disulfide bond that enhanced thermostability. Mutations located in or contacting flexible regions of the protein had a larger stabilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 143 publications
6
54
0
Order By: Relevance
“…These results demonstrate that the strategy not to mutate residues close to the active site was successful for the design of fully active, thermostable LEH‐P variants. Similarly, stabilizing mutations in the dehalogenase LinB only reduced enzyme activity when they were introduced close to the active site . This strategy could be a simple but effective way to maintain catalytic activity during computational design, provided that more distant mutations do not reduce activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate that the strategy not to mutate residues close to the active site was successful for the design of fully active, thermostable LEH‐P variants. Similarly, stabilizing mutations in the dehalogenase LinB only reduced enzyme activity when they were introduced close to the active site . This strategy could be a simple but effective way to maintain catalytic activity during computational design, provided that more distant mutations do not reduce activity.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently explored a strategy termed FRESCO, which uses computational library design, for rapidly increasing the thermostability of enzymes. It was applied to obtain highly thermostable multi‐site mutants of limonene epoxide hydrolase (LEH) from Rhodococcus erythropolis DCL14, and to obtain thermostable and solvent‐resistant mutants of a haloalkane dehalogenase . LEH catalyzes the enantioconvergent production of (1 S ,2 S ,4 R ) limonene‐1,2‐diol from (4 R )‐limonene‐1,2‐epoxide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced stability of D311E lipase was due to additional inter-loop interactions, which were indicated by the atomic details of D311E lipase with the observed additional ion pair and hydrogen bond interactions (Ruslan et al, 2012). Mutations located in or contacting flexible regions of the haloalkane dehalogenase LinB had a larger stabilizing effect than mutations outside such regions (Floor et al, 2014). Results of another study demonstrated the enhancement of C. antarctica lipase B kinetic stability by increasing the rigidity of its active site (Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…The original protocol was modified to enable fully automated calculation at the reasonable time, while maintaining high prediction accuracy (Supplementary Table S6). Prediction of eight multiple-point mutants using this modified protocol was validated using the data of FRESCO (44) and identified mutations were compared with another online protein stabilization tool PROSS (17). FireProt and PROSS showed similar predictive power, correctly identifying 29 and 20 potentially stabilizing positions, respectively (Supplementary Table S7).…”
Section: Experimental Validationmentioning
confidence: 99%